2015
DOI: 10.1007/s00414-015-1277-0
|View full text |Cite
|
Sign up to set email alerts
|

The formation of adipocere in model aquatic environments

Abstract: An examination of the chemistry of adipocere formation in aquatic systems provides insight into how environmental factors affect the decomposition processes of human remains. Gas chromatography–mass spectrometry (GC-MS) and inductively coupled plasma–mass spectrometry (ICPMS) have been employed to monitor the changes to the chemistry of adipocere formed in aquatic environments used to model seawater, river and chlorinated water systems. Seawater was shown to inhibit adipocere formation, and a distinctively dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Continued research into the elemental composition of adipocere may aid in further distinguishing adipocere samples into the different stages of formation: early, intermediate and late stage, and may also be useful to differentiate between different water environments in which adipocere has formed. Chemical analysis of the environment in which adipocere forms is also necessary to further understand the variables, such as pH, presence of oxygen, bacteria and water flow, that influence formation 58 . Furthermore, research in the area of adipocere degradation is suggested, especially with focus on the biochemical pathways and environmental influences that govern adipocere formation 42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Continued research into the elemental composition of adipocere may aid in further distinguishing adipocere samples into the different stages of formation: early, intermediate and late stage, and may also be useful to differentiate between different water environments in which adipocere has formed. Chemical analysis of the environment in which adipocere forms is also necessary to further understand the variables, such as pH, presence of oxygen, bacteria and water flow, that influence formation 58 . Furthermore, research in the area of adipocere degradation is suggested, especially with focus on the biochemical pathways and environmental influences that govern adipocere formation 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Saturation of oleic degradation, the point where the rate of degradation did not increase further, was rapid in distilled and slow in saline. 58 found that seawater inhibits adipocere formation, while river water enhances it.…”
Section: Water Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…One means of examining the decomposition process using fatty acid concentrations is to monitor the transformation of unsaturated to saturated fatty acid concentrations that results from hydrogenation reactions. Such an approach has been used to monitor the formation of the decomposition product adipocere, which is comprised of a mixture of fatty acids [6,14]. Earlier investigations divided the process of adipocere formation into three stages based on the amount of saturated fatty acids present and the % of saturated fatty acids at each stage has been estimated as early (40-60%), intermediate (70-90%) and advanced (>90%).…”
Section: Summer Trialsmentioning
confidence: 99%
“…These processes occur at different intervals. 9 No doubt, these methods depict changes and these changes are correlated with PMI, but multiple researches have shown that these physical changes get influenced by climatic changes, age of deceased, and any underlying disease. 10 Therefore, lack of precision of physical methods led to introduction of biochemical methods.…”
Section: Introductionmentioning
confidence: 99%